Edukasi Bahaya Berita Hoax di Masa Pandemi pada Wali Siswa PAUD RUSA - Ahmad Nugroho; Cristeddy Asa Bakti; Paulus Damar Bayu Murti; Maria Yuliana Belaon (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
During the COVID-19 pandemic, there are a lot of fake news circulating on social media, especially about health, this is what makes people misguided in responding to this pandemic, and results in panic buying. This Community Service aims to make people able to distinguish between fake news and true facts about COVID-19. Moreover, currently the growth of positive cases in Indonesia is increasing. Karangturi National University in collaboration with Rumah Asa held an activity with the theme of the dangers of the internet in terms of spreading hoax news during the pandemic with the parents of students as the target.